Allometric equations for predicting biomass and carbon of Simarouba glauca plantations in dryland of Hyderabad, Telangana - MOHAMED, M B NOOR; RAO, G RAJESHWAR; KUMAR, P SHARATH; REDDY, P SATHI (The Indian Journal of Agricultural Sciences, 2016)
Estimating the carbon stocked in planted forests is important to assess the mitigation effect and to predict potential impact of mechanisms to reduce carbon emissions. This study was conducted in Central Research Institute for Dryland Agriculture, Hyderabad to develop the allometric equations for predicting the above and below ground biomass and total carbon in three different basal diameter classes (0-10 cm, 10-20 cm and 20-30 cm) of Simarouba glauca DC. Higher total biomass of 169.0 kg/tree in 20-30 diameter class followed by 10-20 cm (57.81 kg/tree) diameter class were recorded in S. glauca. From the findings, above ground biomass has a highly significant relationship with tree height, basal diameter, DBH, crown height, crown width. There was a significant linear relationship between below ground biomass and predictors, viz. tree height (0.803), basal diameter (0.820), DBH (0.810), crown height (0.985) and crown width (0.957). And also, strong non-linear relationship (0.985) exists between total biomass and crown height (0.985) followed by crown width (0.957). The allometric coefficients which were calculated from the allometric relations between the biomass of various tree components on total carbon for S. glauca. The highest and strong allometric coefficient registered between total carbon and crown height (0.992) followed by crown width (0.978). This finding may be first for S. glauca in India as no significant literature is available for estimation of biomass and carbon in different components of the species. So the result of this study will be helpful in predicting the amount of carbon credits earned by plantations on area basis, which are requisite under the Kyoto Protocol and REDD policy.